2018
DOI: 10.1093/socrel/sry018
|View full text |Cite
|
Sign up to set email alerts
|

Religion, Support of Equal Rights for Same-Sex Couples and the Australian National Vote on Marriage Equality

Abstract: In 2017, the Australian Government commissioned a national vote on same-sex marriage legislation, which elicited substantial debates dominated by religious voices. We examine the associations between religious identification, importance of religion to one's life and frequency of attendance at religious services and support for same-sex couples in such a unique context. We contribute to knowledge by (i) systematically examining these relationships in a country other than the US (Australia) using high-quality, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…The socio-political context surrounding same-sex sexuality is arguably more liberal in Australia than in the U.S., as evidenced by stronger antidiscrimination protections for sexual minorities (Mendos, 2019) and more positive community attitudes towards same-sex sexuality (McGee, 2016;Pew Research Center, 2013;Valfort, 2017). This may be the product of Australia's more secular and diverse religious landscape (Perales, Bouma, & Campbell, 2018;Stanley, 2015). Crucially, our analyses also speak about changes in sexual identity labels amongst a very recent cohort of emerging adult women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The socio-political context surrounding same-sex sexuality is arguably more liberal in Australia than in the U.S., as evidenced by stronger antidiscrimination protections for sexual minorities (Mendos, 2019) and more positive community attitudes towards same-sex sexuality (McGee, 2016;Pew Research Center, 2013;Valfort, 2017). This may be the product of Australia's more secular and diverse religious landscape (Perales, Bouma, & Campbell, 2018;Stanley, 2015). Crucially, our analyses also speak about changes in sexual identity labels amongst a very recent cohort of emerging adult women.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in 2013, 33% of adults in the U.S. thought that society should not accept homosexuality compared to 18% of adults in Australia (Pew Research Center, 2013). This may be an artefact of differences in the religious landscapes of the two countries, with strong trends towards religious diversification and secularization in Australia over the past few decades (Perales, Bouma, & Campbell, 2018;Stanley, 2015). Our study will therefore provide evidence on sexual identity change in both a more liberal era and a somewhat more liberal country than previous studies.…”
Section: The Australian Contextmentioning
confidence: 99%
“…Particularly, the proportions of Australians with post‐school qualifications (ABS, ) and reporting no religion (ABS, ) are rising, and Australia's biggest cities are experiencing fast growth. On the other hand, Australia's immigrant intake is attracting new arrivals from countries in which identifying with a religion is normative, and this may exert influence in the opposite direction (Perales et al., ). And geography matters.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, previous international scholarship has also reported marked attitudinal divisions by religiosity (Baunach, ; Bramlett, ; Sherkat et al., ). Individuals who identify with a religion are generally less supportive of same‐sex marriage than those who do not identify, which likely stems from the fact that religious teachings often assign negative connotations to same‐sex relations (Perales et al., ). Similar results were obtained for Australia by Perales and Campbell (), who reported that 77.4% of people who did not identify with a religion support equal rights, compared to just 47% of people with no religion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation